Processing temperature and surface Na content of TiO2 nanocrystallites in films for solid-state dye-sensitized solar cells - Feng, Xianjin; Pekkola, René; Mankel, Eric; Lingenfelser, Dominic; Völker, Barbara; Mayer, Thomas; Jaegermann, Wolfram (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
We investigate changes of the chemical surface composition of nanocrystalline TiO2 films induced by systematic temperature variations. Two heating procedures in air are investigated: a hot plate, in similarity to sintering, and an air heating gun, in similarity to activation before staining. Stepwise heated samples have been analyzed at room temperature using synchrotron induced photoelectron spectroscopy and X-ray photoelectron spectroscopy. With increasing temperature, the samples show increasing photoemission of Na-related orbitals. To identify the source of the surface Na—either the soda lime glass substrate or the TiO2 powder itself—we investigate TiO2 films sintered on a Si substrate and films produced from TiO2 powders containing Na from <10 to 170 ppm. Clearly, the TiO2 powder itself is identified as the source of the temperature-enriched Na on the TiO2 crystallites’ surfaces. Efficiency measurements on SDSCs sorted by the Na bulk content corroborate the importance of the Na content for the cell efficiency.